Giving Prizes (reward) and Its Influence on Student Learning Motivation - Faysal, Muh; Tabroni , Imam; Jie , Li; Jixiong, Cai; Nitin, Mahon; Bradford, Snyder (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. Prizes have a very big influence on increasing student learning motivation, because they can generate enthusiasm for student learning. With prizes students can be more motivated and earnest in learning which in the end can also bring better and more optimal results in achieving the learning goals themselves. Purpose. Reward is one method of education. So, by itself the purpose of the reward is as a method for educating children so that children can feel happy because their actions or work are rewarded. Rewards are considered important because rewards can stimulate student enthusiasm for learning. Method. Basically everyone likes to be praised, because of that they need awards which in the world of education can be known in the form of gifts. Prizes are a stimulus for positive things that can generate initiative, energy, self-competence, and can upload student learning motivation. Results. The results of observations at SMP Aql Islamic School Purwakarta that learning still uses the lecture method. In addition, in the learning process, more learning activities are carried out by the teacher, while students are passive and only follow the teacher's orders. Students also still think that Nabawiyah sirah is a boring and scary lesson. Conclusion. This can be seen from the observations that some students talk to themselves with friends, do not want to ask questions and are indifferent to the teacher and are not even enthusiastic about participating in the learning process. Because of that, to increase student learning motivation in the Nabawiyah sirah subject, which in the students' view is difficult to understand because it requires deep concentration, that's why finally the teacher creates innovation by giving gifts when learning takes place. Rewards are fun repressive educational tools, prizes are given to children who have shown good results in education